Comprehensive Decision-Making Method for DC Transformation Object of Medium Voltage AC Distribution Network - Wang, Fengxue; Ou, Yangsen; Xin, Xi; Yang, Moyuan (Frontiers in Energy Research, 2022)
The trend of DC development in medium voltage AC distribution network is obvious. However, due to the constraints of reliability, cost and power quality, not every AC distribution network is suitable for DC transformation. As for the AC distribution network which is suitable for DC transformation, it is necessary to solve the problems of multivariable constraint solution and the demand for sorting and optimizing multi-schemes in DC transformation. Therefore, this paper proposes a comprehensive decision-making method for the DC transformation object of medium voltage AC distribution network. Firstly, a comprehensive evaluation index system for DC transformation is established, which is from four aspects: improving power supply reliability, technical requirements, social benefits and economic benefits. Among them, the reliability of power supply mainly examines the completion degree of the target. In terms of technical requirements of DC transformation, it is necessary to take into account the constraints of AC transformation and the driving force of DC transformation. As for the social benefits, it reflects the indirect demand of DC transformation, which reflects social development. In terms of economic benefits, it pays attention to the transformation cost and input-output ratio. Then, the combined optimization model is used to solve the index’s comprehensive weight, based on the subjective and objective weight model. And the comprehensive evaluation value of the transformation object is determined by the double-base point method. The scheme optimization model is used to determine the final transformation scheme, so as to guide the power grid enterprises to prioritize the DC transformation projects. Finally, several medium-voltage distribution networks in Guangzhou, Guangdong Province, China are taken as examples to verify the effectiveness of the proposed method.